Hi! Your answer is q = -9
Please see an explanation for a better and clear understanding to your problem.
Any questions about my answer and explanation can be asked through comments! :)
Step-by-step explanation:
Since we want to solve for q-term. That means we are going to isolate q-term.
![\huge{3q+4+9=-14}](https://tex.z-dn.net/?f=%5Chuge%7B3q%2B4%2B9%3D-14%7D)
We can add 4 and 9 together.
![\huge{3q+13=-14}](https://tex.z-dn.net/?f=%5Chuge%7B3q%2B13%3D-14%7D)
Because we want to know the value of q. That means we have to isolate q-term by subtracting both sides by 13.
![\huge{3q+13-13=-14-13}\\\huge{3q=-27}](https://tex.z-dn.net/?f=%5Chuge%7B3q%2B13-13%3D-14-13%7D%5C%5C%5Chuge%7B3q%3D-27%7D)
We are reaching to the final step where we divide the whole equation by 3.
![\huge{\frac{3q}{3}=-\frac{27}{3}}\\\huge{q=-9}](https://tex.z-dn.net/?f=%5Chuge%7B%5Cfrac%7B3q%7D%7B3%7D%3D-%5Cfrac%7B27%7D%7B3%7D%7D%5C%5C%5Chuge%7Bq%3D-9%7D)
Finally, the solution for this equation is q = -9. But what if you are not certain or sure about the answer? Let's check it out!
To check the answer, simply substitute q = -9 in the equation.
![\huge{3q+4+9=-14}\\\huge{3(-9)+13=-14}\\\huge{-27+13=-14}\\\huge{-14=-14}](https://tex.z-dn.net/?f=%5Chuge%7B3q%2B4%2B9%3D-14%7D%5C%5C%5Chuge%7B3%28-9%29%2B13%3D-14%7D%5C%5C%5Chuge%7B-27%2B13%3D-14%7D%5C%5C%5Chuge%7B-14%3D-14%7D)
Notice that the equation is true for q = -9. Hence, we can conclude that the solution for this equation is q = -9.
Hope this helps!
<span><span>Simpliest form is a^2/a^2 to get 1
</span></span>
Yes. Think of it like this. You borrowed $1 from your friend for a candy bar. You now have -$1 because you owe your friend money. If you ask your friend for another $5 because you found another thing you wanted you have -$6. When you already have a negative, you are subtracting even more from that, which brings you to an even higher negative number